Malaria risk mapping in Sri Lanka: Implications for its use in control - Proceedings of a workshop held at the International Water Management Institute, Colombo, 25 May 2001 - Klinkenberg, Eveline (International Water Management Institute, 2001)
This working paper contains the proceedings of the workshop on ?Malaria risk mapping in Sri Lanka?implications for its use in control? that was held on May 25, 2001 at IWMI Headquarters in Colombo, which was a follow up to the workshop conducted on March 29, 2001 in Embilipitiya (Klinkenberg 2001). The workshop in Embilipitiya was organized at the local level to discuss the results of the malaria risk mapping work carried out by IWMI in the Uda Walawe region of Sri Lanka. Participants at this workshop were local health staff involved in malaria control work in the area and officials from the Land Use Planning Offices and Divisional Secretariats.